Materialien zur Documenta X : Ein Reader für Unterricht und Studium - Ammann, Jean-Christophe; Balkenhol, Bernhard; Baudrillard, Jean; Baum, Klaus; Blohm, Manfred; Borchers, Peter; David, Catherine; Dommer, Eckhard; Fuchs, Christine; Grauer, Michael; Grützmacher, Elke; Hellstern, Gerd-Michael; et al. (Ostfildern-Ruit : Cantz Verlag, 1997)
Mondriaan, Piet ; Bolsmann, Birgitt ; Roosen, Maria ; Burden, Chris ; Koons, Jeff ; Wall, Jeff ; Müller, Christian Philipp ; Caillebotte, Gustave ; Bourgeois, Louise ; Nicolai, Olaf ; Buren, Daniel ; Merz, Gerhard ; Rockenschaub, Gerwald ; Lawler, Louise ; Struth, Thomas ; Art & Language ; Kosuth, Joseph ; Close, Chuck ; Metzel, Olaf ; Mosler, Mariella ; Orozco, Gabriel ; Marshall, Kerry James ; Zittel, Andrea ; Ngui, Mathew ; Höller, Carsten ; Trockel, Rosemarie ; Graham, Dan ; Tunga ; Richter, Gerhard ; Broodthaers, Marcel ; Matta-Clark, Gordon ; Levitt, Helen ; Muybridge, Eadweard ; Pistoletto, Michelangelo ; Hamilton, Richard ; Fischli & Weiss ; Lafont, Suzanne ; Acconci, Vito ; Höller, Carsten ; Oursler, Tony ; Hill, Christine ; Müller, Christian Philipp ; Beuys, Joseph ; Long, Richard ; Kiefer, Anselm ; Baumgarten, Lothar ; Haacke, Hans ; Kogler, Peter ; Kabakov, Ilya ; Opalka, Roman ; Borofsky, Jonathan ; Voth, Hannsjörg ; Toroni, Niele ; Armleder, John M. ; Scholte, Rob
Documenta X, Kassel, 21.06 - 28.09.1997
Duits
boek